Data for Observations of Contact Resistance in TOPCon and PERC Solar Cells - Liu, D; Wright, M; Goodarzi, M; Wilshaw, P R; Hamer, P; Bonilla, R S (University of Oxford, 2022)
Data acquired for the publication of Observations of Contact Resistance in TOPCon and PERC Solar Cells Abstract – In this article we investigate the observation of increased contact resistance in both PERC and TOPCon solar cells linked to hydrogen dynamics at the interface. We study the changes in series resistance (RS) as a result of applied forward and reverse bias in the temperature range from 350 °C – 400 °C. In PERC cells, we use a modified geometry to isolate the root cause of the increased RS by isolating the current path through the different parts of the cell. We show that contact resistance in PERC cells occurs between the Ag contact and the n+ silicon region at the front surface. We also report the first observation of contact resistance in industrial n-type TOPCon solar cells. For both PERC and TOPCon cells, we show that the temperature of the measurement has a profound impact on the amount of contact resistance. However, the response of the two cell architectures under varied biasing conditions is not identical. TLM measurements reveal that in TOPCon cells the increased RS is caused by the Ag contact to the n+ polysilicon region, which, unlike in PERC cells, corresponds to the rear surface, away from the p-n junction. Recent results have shown that severe surface-related degradation in TOPCon solar cells can be mitigated by annealing treatments at temperatures similar to those explored herein. Therefore, identifying contact resistance in TOPCon cells may have a profound impact on further studies exploring degradation mitigation pathways in TOPCon cells.